2020
DOI: 10.3390/molecules25204784
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fungal Dextranase Production and Its Antibiofilm Activity, Encapsulation and Stability in Toothpaste

Abstract: Dextranase catalyzes the degradation of the substrate dextran, which is a component of plaque biofilm. This enzyme is involved in antiplaque accumulation, which can prevent dental caries. The activity of crude dextranase from Penicillium roquefortii TISTR 3511 was assessed, and the maximum value (7.61 unit/g) was obtained at 37 °C and pH 6. The Plackett–Burman design was used to obtain significant factors for enhancing fungal dextranase production, and three influencing factors were found: Dextran, yeast extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Others have found similar findings, e.g., microencapsulation of S. boulardii in Ch-coated Alg beads. 36 , 37 A study by Juntarachot et al 38 showed that encapsulation of dextranase in Alg beads increased the stability for up to 3 months without any significant change in their activity. Koo et al 20 speculated that coating of Alg beads with Ch improved the chemical and mechanical strength of the beads and allowed for longer-term storage.…”
Section: Resultsmentioning
confidence: 99%
“…Others have found similar findings, e.g., microencapsulation of S. boulardii in Ch-coated Alg beads. 36 , 37 A study by Juntarachot et al 38 showed that encapsulation of dextranase in Alg beads increased the stability for up to 3 months without any significant change in their activity. Koo et al 20 speculated that coating of Alg beads with Ch improved the chemical and mechanical strength of the beads and allowed for longer-term storage.…”
Section: Resultsmentioning
confidence: 99%
“…In sugar industry, dextranase can remove dextran to improve production efficiency, yield, and quality of sucrose (Bhatia et al, 2010(Bhatia et al, , 2016Eggleston et al, 2009;Sufiate et al, 2018;Zhao et al, 2021). Dextranase has many applications in the prevention and treatment of dental caries (Jiao et al, 2014;Juntarachot et al, 2020;Lai et al, 2019;Ren et al, 2016). High molecular dextran can be hydrolyzed by dextranase to prepare low molecular weight compounds or isomaltooligosaccharides (IGs).…”
Section: Dextranasementioning
confidence: 99%
“…There are numerous causes of dextranase instability in oral care products, including temperature, acidity, alkalinity, surfactants, and other oral care product components [ 92 ]. Fungal dextranase is widely used in the food industry as it is safe and easy to obtain after harvesting mushrooms [ 93 ].…”
Section: Comparison Of Dextranases From Marine Bacteria With Those Fr...mentioning
confidence: 99%